Ethico-Aesthetic Repairs: Introduction. Issue 1 (2nd January 2018) - Reeves-Evison, Theo; Rainey, Mark Justin
Abstract: Repairs, like many of the people who carry them out, often constitute an invisible background that ensures the smooth functioning of everyday life-worlds. This extended introduction instead places them centre stage, situating the theory and practice of repair at the intersection of a number of different fields, from Science and Technology Studies to the Medical Humanities. It explores the role repair plays in the layered history of various objects and social forms, from technological devices and artworks, to post-conflict cultures. Repair, it argues, is a practice that exists in relational webs of entanglement, where its power can be multiplied if supplemented with an ethics of care. Like the examples of repair it brings to light, the introduction seeks to hold heterogeneous fragments in relation, positing repair as a 'material metaphor' that is invaluable for posing questions in a range of disciplinary arenas.